2015
DOI: 10.1161/strokeaha.115.010471
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Maintains a State of Heightened Responsiveness to Motor Training Early After Stroke in a Mouse Model

Abstract: Background and purpose Data from both humans and animal models suggest that most recovery from motor impairment occurs in a sensitive period that lasts only weeks after stroke and is mediated in part by an increased responsiveness to training. Here we used a mouse model of focal cortical stroke to test two hypotheses. First we investigated if responsiveness to training decreases over time after stroke. Second, we tested whether fluoxetine, which can influence synaptic plasticity and stroke recovery, can prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 85 publications
3
85
1
Order By: Relevance
“…Specifically, using custom built cages (schematized in Figure 1B – E) we trained wild-type adult male mice to perform a skilled prehension task to an asymptotic level of performance, photothrombotically induced a focal CFA infarction (t1; Figure 2 A and B), and retrained them after a 7-day delay. Assessment on the prehension task on day 18 (eight days after stroke) revealed that there was little spontaneous recovery of performance, which is in agreement with our prior results [7], and subsequent training over 19 days total led to only mild performance gains that never returned to pre-stroke levels (Figure 3A and B days 18 – 36). A second focal stroke was then induced in the ipsilesional medial premotor area (AGm) at time point t2 (figure 2 A and B).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, using custom built cages (schematized in Figure 1B – E) we trained wild-type adult male mice to perform a skilled prehension task to an asymptotic level of performance, photothrombotically induced a focal CFA infarction (t1; Figure 2 A and B), and retrained them after a 7-day delay. Assessment on the prehension task on day 18 (eight days after stroke) revealed that there was little spontaneous recovery of performance, which is in agreement with our prior results [7], and subsequent training over 19 days total led to only mild performance gains that never returned to pre-stroke levels (Figure 3A and B days 18 – 36). A second focal stroke was then induced in the ipsilesional medial premotor area (AGm) at time point t2 (figure 2 A and B).…”
Section: Resultssupporting
confidence: 91%
“…during days 18–36) that we saw here in the mouse is consistent with studies in the rat that failed to show a benefit of late tune-ups despite a response to training early after stroke [20]. That the impact of training falls off rapidly within one week post-stroke is consistent with our prior results [7] and also consistent with results in rats showing only a modest response to training and enrichment given 2 weeks post-stroke, compared to when given early [1]. Human data also suggest a short-lived plasticity window after stroke with most spontaneous recovery, which follows a predictable proportionality rule [3, 21], occurring in the first 3 months [4, 22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Proficiency in other motor tests appears to improve spontaneously after injury, especially when end-point measures are used. Indeed, it has been clearly shown that sensory-motor performances (including reaching success in the pellet grasping task) improve already after 2 weeks3940414243.…”
Section: Resultsmentioning
confidence: 99%
“…However, controversy over fluoxetine’s exact mechanism of action in stroke remains. Although fluoxetine may increase neurogenesis (Corbett et al 2015; Imoto et al 2015; Sun et al 2015), its beneficial effect in stroke may be due to reducing inhibitory interneuron expression in the premotor cortex (Ng et al 2015). Nonetheless, taken together, it may be suggested that elevated levels of neurotrophins in general and BDNF in particular following antidepressants administration are at least partially responsible for the enhanced neurogenesis and hence beneficial effects in neurodegenerative diseases such as AD.…”
Section: Neuroprotection By Current Antidepressants and Involvement Omentioning
confidence: 99%